Seasonal changes in fatty acid profile of the freshwater snail Viviparus contectus (Millet, 1813) from lake habitat - Ozcicek, Esin; Kocabas, Filiz Kutluyer; Kocabas, Mehmet; Yilmaz, Okkes (Taylor & Francis Ltd, 2023)
The freshwater snail, Viviparus contectus, is an important shellfish owing to its nutritional composition (i.e., high amounts of protein, essential amino acids, fatty acid profile and minerals) and its promise as a candidate for the treatment of some diseases in traditional medicine. Hence, the seasonal changes in the fatty acid (FA) profile of Viviparus contectus caught from Demirkopru Dam Lake were determined in this study. Saturated fatty acid (SFAs) (64.54-80.39% of total fatty acids) had the highest concentration followed by polyunsaturated fatty acids (PUFAs) (10.63-21.83%) and monounsaturated fatty acids (MUFAs) (6.57-10.13%). Stearic acid (C18:0) was the major SFA while arachidonic acid (C20:4 n-6) was the major PUFA. The season significantly affected the FA profile of V. contectus while no significant difference was determined between seasons with respect to tissue MUFAs levels. A higher level of total SFAs was detected during spring (80.39%) while a higher proportion of MUFAs was detected during the winter (10.13%). The total amounts of PUFAs were highest in winter (21.83%). Overall, V. contectus has nutritional value. However, V. contectus caught in autumn may be nutritionally the most valuable for human consumption due to higher eicosapentaenoic acid 20:5 n-3 and docosahexaenoic acid contents.
Keywords: Demirkopru Dam Lake; nutritional composition; season; shellfish